Neuroinflammation Is Aggravated by the Aqueous Extract of Myrmecodia Platytyrea Tuber - Ashish Kushwaha; Ritik Srivastava; Arun K. Maurya; Lalit Bisht; Arvind Negi; Kirti Kumari; Mohit Pal; Shipra Omar; Abhishek Chauhan (International Journal of Brain Sciences, 2026)
Myrmecodia platytyrea, commonly known as the ant plant, is a medicinal epiphyte traditionally used in Southeast Asia for its purported health benefits, including anti-inflammatory, antioxidant, antimicrobial, and anticancer activities. Its tuber contains abundant secondary metabolites, including flavonoids, tannins, phenolic compounds, and saponins. While these phytochemicals are generally associated with therapeutic effects, the biological activity of Myrmecodia extracts varies depending on the type of extract, dosage, and route of administration. In contrast to the commonly assumed anti-inflammatory properties of many plant-derived compounds, recent studies indicate that some aqueous extracts can produce unexpected or harmful effects under certain disease conditions. The influence of Myrmecodia platytyrea tuber extract on neuroinflammation remains largely unexplored. Methods: Astrocyte cytotoxicity was assessed using the MTT assay. The impact of MPAE at concentrations between 0.025 and 0.5 mg/mL was evaluated on reactive oxygen species (ROS) generation and the secretion of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) in astrocyte cultures stimulated with Fe₂SO₄, H₂O₂, and LPS. Results: MPAE exhibited no cytotoxic effects on astrocytes under baseline conditions. However, it failed to confer protection against oxidative or inflammatory stress induced by Fe₂SO₄, H₂O₂, or LPS. In contrast, MPAE treatment led to increased astrocyte death and elevated ROS and cytokine levels in a dose-dependent fashion. Conclusion: While MPAE does not exhibit inherent cytotoxicity, its ability to amplify neuroinflammation in vitro raises important safety concerns—particularly for elderly individuals using this plant to alleviate inflammatory symptoms. These findings underline the necessity for further in-depth research to assess its safety and therapeutic potential before considering it for neurodegenerative disease treatment.
Keywords: Myrmecodia platytyrea; Oxidative stress; astrocytes; neuroinflammation; pro-oxidant